Sobre el pintor de cámara Santiago Morán el Viejo (1571-1626) - Cruz Valdovinos, José Manuel (Anales de Historia del Arte, 2008)
From several published news and other unpublished ones, pieces of information and facts concerning Santiago Morán old and his namesake son, including their date and place of birth and death, as well as the relations with the former’s master, Pantoja de la Cruz, considering the office Chamber painter and vicissitudes of the Florentine painting from the Descalzas Reales in Valladolid, are presented.